Check the below NCERT MCQ Questions for Class 7 Maths Chapter 4 Simple Equations with Answers Pdf free download. MCQ Questions for Class 7 Maths with Answers were prepared based on the latest exam pattern. We have provided Simple Equations Class 7 Maths MCQs Questions with Answers to help students understand the concept very well. https://ncertmcq.com/mcq-questions-for-class-7-maths-with-answers/

Students can also refer to NCERT Solutions for Class 7 Maths Chapter 1 Simple Equations for better exam preparation and score more marks.

## Simple Equations Class 7 MCQs Questions with Answers

Simple Equations Class 7 MCQ Question 1.
Write the following statement in the form of an equation:
The sum of three times x and 10 is 13.
(a) 3x + 10 = 13
(b) 3x – 10 = 13
(c) 3x + 13 = 10
(d) none of these

Answer: (a) 3x + 10 = 13

Class 7 Maths Chapter 4 MCQ Question 2.
Write the following statement in the form of an equation:
If you subtract 3 from 6 times a number, you get 9
(a) 3x – 6 = 9
(b) 6x – 3 = 9
(c) 6x + 3 = 9
(d) 3x + 6 = 9

Answer: (b) 6x – 3 = 9

MCQ Questions For Class 7 Maths Chapter 4 Question 3.
Write the following statement in the form of an equation:
One fourth of n is 3 more than 2
(a) $$\frac { n }{ 4 }$$ – 2 = 3
(b) $$\frac { n }{ 4 }$$ + 2 = 3
(c) $$\frac { n }{ 2 }$$ – 4 = 3
(d) $$\frac { n }{ 2 }$$ + 4 = 3

Answer: (a) $$\frac { n }{ 4 }$$ – 2 = 3

MCQ On Simple Equations For Class 7 Question 4.
Write the following statement in the form of an equation:
One third of a number plus 2 is 3
(a) $$\frac { m }{ 3 }$$ – 2 = 3
(b) $$\frac { m }{ 3 }$$ + 2 = 3
(c) $$\frac { m }{ 2 }$$ – 3 = 3
(d) $$\frac { m }{ 2 }$$ + 3 = 3

Answer: (b) $$\frac { m }{ 3 }$$ + 2 = 3

Class 7 Maths Chapter 4 MCQ With Answers Question 5.
Write the following statement in the form of an equation:
Taking away 5 from x gives 10
(a) x – 5 = 10
(b) x + 5 = 10
(c) x – 10 – 5
(d) none of these

Answer: (a) x – 5 = 10

Class 7 Maths Ch 4 MCQ Question 6.
Write the following statement in the form of an equation:
Four times a number p is 8.
(a) 4P = 8
(b) P + 4 = 8
(c) p – 4 = 8
(d) p ÷ 4 = 8

Class 7 Math Chapter 4 MCQ Question 7.
Write the following statement in the form of an equation:
Add 1 to three times n to get 7
(a) 3n + 1 = 7
(b) 3n – 1 = 7
(c) 3n + 7 = 1
(d) none of these

Answer: (a) 3n + 1 = 7

Simple Equations MCQ Class 7 Question 8.
Write the following statement in the form of an equation:
The number b divided by 6 gives 5.
(a) $$\frac { b }{ 6 }$$ = 5
(b) b – 5 = 6
(c) 5b = 6
(d) b + 5 = 6

Answer: (a) $$\frac { b }{ 6 }$$ = 5

Class 7 Simple Equations MCQ Question 9.
The solution of the equation x + 3 = 0 is
(a) 3
(b) -3
(c) 0
(d) 1

Hint:
x + 3 = 0 ⇒ x = -3.

MCQ Questions On Simple Equations For Class 7 Question 10.
The solution of the equation x – 6 = 1 is
(a) 1
(b) 6
(c) -7
(b) 7

Hint:
x – 6 = 1 ⇒ x = 1 + 6 = 7.

Class 7th Maths Chapter 4 MCQ Question 11.
The solution of the equation 5x = 10 is
(a) 1
(b) 2
(c) 5
(d) 10

Hint:
5x = 10 ⇒ x = $$\frac{10}{5}$$ = 2

MCQ Questions For Class 7 Maths Simple Equations Question 12.
The solution of the equation $$\frac { m }{ 2 }$$ = 3 is
(a) 2
(b) 3
(c) 12
(d) 6

Hint:
$$\frac{m}{2}$$ = 3 ⇒ m = 3 × 2 = 6.

Class 7 Maths Chapter 4 MCQ Online Test Question 13.
The solution of the equation 7n + 5 = 12 is
(a) 0
(b) – 1
(c) 1
(d) 5

Hint:
7n + 5 = 12 ⇒ 7n = 12 – 5
⇒ 7n = 1 ⇒ n = $$\frac{7}{7}$$ = 1.

Class 7 Chapter 4 Maths MCQ Question 14.
The solution of the equation 4p – 3 = 9 is
(a) 1
(b) 2
(c) 3
(d) 4

Hint:
4p – 3 = 9 ⇒ 4p = 9 + 3 = 12
⇒ p = $$\frac{12}{4}$$ = 3.

MCQ Class 7 Maths Chapter 4 Question 15.
The solution of the equation 5p + 2 = 7 is
(a) 0
(b) 1
(c) -1
(d) 2

Hint:
5p + 2 = 71 ⇒ 5p = 7 – 2 = 5
⇒ p = $$\frac{5}{5}$$ = 1.

Question 16.
The solution of the equation 3p – 2 = 4 is
(a) 0
(b) 1
(c) 2
(d) 3

Hint:
3p – 2 = 4 ⇒ 3p = 4 + 2 = 6
⇒ P = $$\frac{6}{3}$$ = 2

Question 17.
The solution of the equation p + 4 = 4 is
(a) 0
(b) 4
(c) -4
(d) 8

Hint:
p + 4 = 4 ⇒ P = 4 – 4 = 0.

Question 18.
The solution of the equation m – 1 = 2 is
(a) 1
(b) 2
(c) 3
(d) 6

Hint:
m – 1 = 2 ⇒ m = 2 + 1 = 3.

Question 19.
The solution of the equation 2m = 4 is
(a) 1
(b) 2
(c) -1
(d) -2

Hint:
2m = 4 ⇒ m = $$\frac{4}{2}$$ = 2

Question 20.
The solution of the equation $$\frac { m }{ 3 }$$ = 3 is
(a) 3
(b) 6
(c) 9
(d) 12

Hint:
$$\frac{m}{3}$$ = 3 ⇒ m = 3 × 3 = 9.

Question 21.
The solution of the equation = 6 is
(a) 6
(b) 7
(c) 14
(d) 3

Hint:
$$\frac{3m}{7}$$ = 6 ⇒ 3m = 7 × 6 = 42
⇒ m = $$\frac{42}{3}$$ = 14

Question 22.
The solution of the equation 3p + 5 = 8 is
(a) -1
(b) 1
(c) 3
(d) 5

Hint:
3p + 5 = 8 ⇒ 3p = 8 – 5 = 3
⇒ P = $$\frac{3}{3}$$ = 1 4p – 2 = 10

Question 23.
The solution of the equation 4p – 2 = 10 is
(a) 1
(b) 2
(c) 3
(d) 4

Hint:
4p – 2 = 10 ⇒ 4p = 10 + 2 = 12
⇒ p = $$\frac{12}{4}$$ = 3.

Question 24.
The solution of the equation $$\frac { p }{ 2 }$$ + 1 = 3 is
(a) 1
(b) 2
(c) 3
(d) 4

Hint:
$$\frac{p}{2}$$ + 1 = 3 ⇒ $$\frac{p}{2}$$ = 3 – 1 = 2
p = 2 × 2 = 4

Question 25.
The solution of the equation 3 m + 7=16 is
(a) 1
(b) 2
(c) 3
(d) 4

Hint:
3m + 7 = 16 ⇒ 3m = 16 – 7 = 9
⇒ m = $$\frac{9}{3}$$ = 3

Question 26.
The solution of the equation 2p – 1 = 3 is
(a) 1
(b) 2
(c) 3
(d) 4

Hint:
2p – 1 = 3 ⇒ 2p = 3 + 1 = 4
⇒ p = $$\frac{4}{2}$$ = 2.

Question 27.
The solution of the equation 4x + 5 = 9 is
(a) 1
(b) 2
(c) 3
(d) 4

Hint:
4x + 5 = 9 ⇒ 4x = 9 – 6 = 4
⇒ x = $$\frac{4}{4}$$ = 1.

Question 28.
The solution of the equation 10 y – 20 = 30 is
(a) 1
(b) 2
(c) 3
(d) 5

Hint:
10y – 20 = 30 ⇒ 10y = 30 + 20 = 50
⇒ y = $$\frac{50}{10}$$ = 5.

Question 29.
The solution of the equation y – 4 = – 1 is
(a) 1
(b) 2
(c) 3
(d) 4

Hint:
y – 4 = -1 ⇒ y = 4 – 1 = 3.

Question 30.
The solution of the equation y + 2 = -2 is
(a) 2
(b) -2
(c) 4
(d) -4

Hint:
y + 2 = -2 ⇒ y = -2 – 2 = -4.

Question 31.
The solution of the equation 10t = -20 is
(a) 1
(b) -1
(c) 2
(d) -2

Hint:
10t = -20 ⇒ t = –$$\frac{20}{10}$$ = -2

Question 32.
The solution of the equation $$\frac { z }{ 2 }$$ = $$\frac { 3 }{ 4 }$$ is
(a) $$\frac { 1 }{ 2 }$$
(b) $$\frac { 3 }{ 2 }$$
(c) $$\frac { 1 }{ 4 }$$
(d) $$\frac { 3 }{ 4 }$$

Answer: (b) $$\frac { 3 }{ 2 }$$
Hint:
$$\frac{z}{2}$$ = $$\frac{3}{4}$$ ⇒ z = $$\frac{3×2}{4}$$ = $$\frac{3}{2}$$

Question 33.
The solution of the equation 2s = 0 is
(a) 2
(b) -2
(c) 0
(d) $$\frac { 1 }{ 2 }$$

Hint:
2s = 0 ⇒ s = $$\frac{0}{2}$$ = 0.

Question 34.
The solution of the equation – $$\frac { p }{ 7 }$$ = 3 is
(a) -3
(b) -7
(c) -21
(d) 21

Hint:
–$$\frac{p}{7}$$ = 3 ⇒ -p = 3 × 7 = 21
⇒ p = -21

Question 35.
The solution of the equation 3s + 6 = 0 is
(a) 1
(b) -1
(c) 2
(d) -2

Hint:
3s + 6 = 0
⇒ 3s = -6 ⇒ s = –$$\frac{6}{3}$$ = -2.

Question 36.
The solution of the equation 10p = 10 is
(a) 1
(b) – 1
(c) 10
(d) – 10

Hint:
10p = 10 ⇒ p = $$\frac{10}{10}$$ = 1.

Question 37.
The solution of the equation 10p + 10 = 110 is
(a) 10
(b) -10
(c) 100
(d) 110

Hint:
10p + 10 = 110
⇒ 10p = 110 – 10 = 100
⇒ p = $$\frac{100}{10}$$ = 10.

Question 38.
The solution of the equation 12p – 11 = 13 is
(a) 1
(b) 2
(c) 3
(d) 4

Hint:
12p – 11 = 13 ⇒ 12p = 13 + 11 = 24
⇒ p = $$\frac{24}{12}$$ = 2.

Question 39.
The solution of the equation 2 (m + 3) = 8 is
(a) 1
(b) 2
(c) 3
(d) 4

Hint:
2(m + 3) = 8 ⇒ m + 3 = $$\frac{8}{2}$$ = 4
⇒ m = 4 – 3 = 1.

Question 40.
The solution of the equation – 2(x + 3) = 4 is
(a) -2
(b) -3
(c) -4
(d) -5

Hint:
-2 (x + 3) = 4 ⇒ x + 3 = $$\frac{4}{-2}$$ = -2
⇒ x = -2 – 3 = -5.

Question 41.
The solution of the equation $$\frac { 5 }{ 2 }$$ x = 15 is
(a) 2
(b) 4
(c) 6
(d) 10

Hint:
$$\frac{5}{2}$$ x = 15 ⇒ x = $$\frac{15×2}{5}$$ = 6

Question 42.
The solution of the equation 4(2 – x) = 4 is
(a) 1
(b) 2
(c) 3
(d) 4

Hint:
4 (2 – x) = 4 ⇒ 2 – x = $$\frac{4}{4}$$ = 1
⇒ x = 2 – 1 = 1.

Question 43.
The solution of the equation -4(2 + x) = 4 is
(a) -1
(b) -2
(c) -3
(d) -4

Hint:
-4(2 + x) = 4 ⇒ 2 + x = $$\frac{4}{-4}$$ = -1
⇒ x = -1 – 2 = -3.

Question 44.
The solution of the equation – 4 = 2 (p – 2) is
(a) 0
(b) 1
(c) 2
(d) 4

Hint:
-4 = 2(p – 2) ⇒ p – 2 = –$$\frac{4}{2}$$ = -2
⇒ p = -2 + 2 = 0.

Question 45.
The solution of the equation 0 = 4 + 4(m + 1) is
(a) 1
(b) -1
(c) 2
(d) -2

⇒ 4(m + 1) = -4 ⇒ m + 1 = –$$\frac{4}{4}$$ = -1